Pulsar astronomy - Lyne, A. G.; Graham-Smith, Francis, 1923- (Cambridge astrophysics series, 2012)
"Over the last 40 years, an astonishing range of astrophysics has become accessible through pulsar astronomy. The body of literature on this rapidly growing research area is vast and observational techniques now cover the whole of the electromagnetic spectrum. Now in its fourth edition, this authoritative volume gives a thorough introduction to the field. It is extensively revised throughout and new material includes: astrometry of binary pulsars and relativity theory; millisecond pulsars; the origin and Galactic population of pulsars and magnetars; and the pulsed emission from radio to gamma-rays. Within each topic, the authors concentrate on the fundamental physics and list extensive references, spanning from first discoveries to the most recent advances. Websites for catalogues of known pulsars are also recommended, providing a basis for new research work. The rapid pace of progress in pulsar astronomy makes this essential reading both for advanced students entering the field and established researchers"--Provided by publisher